Dengue Protease Substrate Recognition: Binding of the Prime Side - Lin, Kuan-Hung (ACS Infect Dis, 2016)
Dengue virus (DENV), transmitted predominantly in tropical and subtropical regions by the mosquito Aedes aegypti, infects millions of people and leads to dengue fever and thousands of deaths each year. There are no direct-acting antivirals to combat DENV, and molecular and structural knowledge is required to develop such compounds. The dengue NS2B/NS3 protease is a promising target for direct-acting antivirals, as viral polyprotein cleavage during replication is required for the maturation of the viral particle. The NS2B/NS3 protease processes 8 of the 13 viral polyprotein cleavage sites to allow viral maturation. Although these sites share little sequence homology beyond the P1 and P2 positions, most are well conserved among the serotypes. How the other substrate residues, especially at the P′ side, affect substrate recognition remains unclear. We exploited the tight-binding general serine protease inhibitor aprotinin to investigate protease–substrate interactions at the molecular level. We engineered aprotinin’s binding loop with sequences mimicking the P′ side of DENV substrates. P′ residues significantly modulate substrate affinity to protease, with inhibition constants varying from nanomolar to sub-millimolar. Structural and dynamic analysis revealed the molecular basis of this modulation and allowed identifying optimal residues for each of the P′ positions. In addition, isothermal titration calorimetry showed binding to be solely entropy driven for all constructs. Potential flaviviral P′ side inhibitors could benefit from mimicking the optimal residues at P′ positions and incorporate hydrophobicity and rigidity to maintain entropic advantage for potency.